Imaging-Based Diagnosis of an Ectopic Submandibular Gland: A Rare Clinical Presentation - Awan , Muhammed; Kashbour, Muataz (AlQalam Journal of Medical and Applied Sciences, 2025)
Ectopic submandibular gland (SMG) is a rare developmental anomaly that can mimic other neck masses, leading to diagnostic challenges. We presented a rare case with a right-sided ectopic SMG. A 52-year-old female presented with a 1-year history of chronic mouth dryness (xerostomia) and intermittent dysphagia. Ultrasound revealed an abnormal position of the SMG; contrast-enhanced magnetic resonance imaging (MRI) confirmed a right-sided ectopic SMG located lateral and superior to the thyroid lobe with dilatation of Wharton’s duct and features suggestive of acalculous sialadenitis. A minor salivary gland biopsy performed to exclude Sjögren’s syndrome showed mild lymphocytic infiltration without autoimmune features. As no obstructive or autoimmune pathology was identified, the patient was managed conservatively with symptomatic treatment and scheduled for regular follow-up. An ectopic SMG is a rare anomaly that can mimic other neck or salivary pathologies. High-resolution imaging is essential for diagnosis, while histopathology may be helpful when autoimmune disease is suspected. Awareness of this condition helps prevent unnecessary invasive procedures and supports appropriate conservative management.